Recovery units under the Endangered Species Act should be used more widely - Evans, Michael J.; Malcom, Jacob W. (Frontiers in Conservation Science, 2022)
Recovering species is the main goal of the Endangered Species Act (ESA). In the face of limited conservation budgets, diverse tools are needed to efficiently recover species. Recovery units may be one such tool - designated portions of a species’ range that must be recovered individually before an entire species can be considered recovered. Recovery units allow for spatial flexibility in developing recovery goals and may be used in regulatory decisions such as ESA section 7 consultation. Despite the advantages, very little information exists on how recovery units have been developed and used. We mined available public data to determine the number and types of species for which recovery units have been designated; evaluated species and geographic characteristics associated with recovery unit designation; and examined how recovery units have been used in implementing the ESA, such as during consultation. We found 49 listed species had designated recovery units through December 2017, and that these species typically had relatively large ranges and were well-studied. We found taxonomic biases in recovery unit designation as well, with fish species being disproportionately likely to have recovery units and plants disproportionately less. These species were also more likely to have their recovery units considered and used in subsequent ESA implementation – a probability that decreased as time since unit designation passed. Improvements in recovery priority numbers among species with recovery units indicate that the theoretical benefits of this tool may have translated to improved status. These data indicate that recovery units could be applied to additional wide-ranging species to improve recovery under the ESA.